Physical and anthropometric changes during pre- and in-season in professional soccer players - Fessi, M. S.; Zarrouk, N.; Filetti, C.; Rebai, H.; Elloumi, M.; Moalla, W. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to examine the changes in anthropometric and physical fitness characteristics in professional soccer players at the beginning of the season, after preseason camp and during in-season.